2010
DOI: 10.1103/physrevlett.105.137801
|View full text |Cite
|
Sign up to set email alerts
|

Charge Ordering Induces a Smectic Phase in Oblate Ionic Liquid Crystals

Abstract: We report a computer simulation study of an electroneutral mixture of oppositely charged oblate ellipsoids of revolution with aspect ratio A=1/3. In contrast with hard or soft repulsive ellipsoids, which are purely nematic, this system exhibits a smectic-A phase in which charges of equal sign are counterintuitively packed in layers perpendicular to the nematic director.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…We conclude that the ionic smectic A phase is formed (counter-intuitively) with significantly lower value of the molecular order parameter S when comparing to non-ionic smectic mesogens [20][21][22]. Theoretical and computational studies suggest that, in contrast to neutral mesogens, the orientational ordering is less important for the stabilization of the smectic layers in ILC where dominant stabilizing effect is due to a "charge-ordered" nanoscale segregation induced by ionic interactions [1,19,23,24]. In order to analyse the dipolar couplings and local bond order parameters in the imidazolium core (Figure 4a), the molecular axis alignment to imidazolium ring plane has to be correctly accounted for.…”
Section: Order Parametersmentioning
confidence: 79%
“…We conclude that the ionic smectic A phase is formed (counter-intuitively) with significantly lower value of the molecular order parameter S when comparing to non-ionic smectic mesogens [20][21][22]. Theoretical and computational studies suggest that, in contrast to neutral mesogens, the orientational ordering is less important for the stabilization of the smectic layers in ILC where dominant stabilizing effect is due to a "charge-ordered" nanoscale segregation induced by ionic interactions [1,19,23,24]. In order to analyse the dipolar couplings and local bond order parameters in the imidazolium core (Figure 4a), the molecular axis alignment to imidazolium ring plane has to be correctly accounted for.…”
Section: Order Parametersmentioning
confidence: 79%
“…Hence, water promotes diffusion within the layers to a larger extent compared to that in the perpendicular direction. In smectic ILCs, the dominant layer-stabilising effect is due to a 'charge-ordered' nanoscale segregation induced by ionic interactions, while the orientational ordering is less important [1,41,48,49]. Water molecules contribute further to the structure stabilisation by the formation of a hydrogen bonding network in the ionic sub-layers [1].…”
Section: Diffusion In a Smectic A Phase Of A Hydrated C 12 Mimclmentioning
confidence: 99%
“…Additionally, the phase diagram in hydroscopic ILCs is affected by water-anion hydrogen bonding [1,6,9]. Theoretical and experimental studies of orientational order in ILCs [1,[10][11][12][13][14] revealed that, due to the contribution of the electrostatic interactions to the stabilization of layered structures, smectic phases in ILCs exhibit significantly lower value of the molecular orientational order parameter S as compared to that in its non-ionic counterparts. However, systematic studies of the orientational order parameter depending on ILCs structure and ionic composition are still lacking.…”
Section: Introductionmentioning
confidence: 99%